2013
DOI: 10.1074/mcp.m113.030700
|View full text |Cite
|
Sign up to set email alerts
|

Specific Glycoforms of MUC5AC and Endorepellin Accurately Distinguish Mucinous from Nonmucinous Pancreatic Cysts

Abstract: Specific protein glycoforms may be uniquely informative about the pathological state of a cyst and may serve as accurate biomarkers. Here we tested that hypothesis using antibody-lectin sandwich arrays in broad screens of protein glycoforms and in targeted studies of candidate markers. We profiled 16 different glycoforms of proteins captured by 72 different antibodies in cyst fluid from mucinous and nonmucinous cysts (n ‫؍‬ 22), and we then tested a three-marker panel in 22 addition samples and 22 blinded samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…9-11 Investigating and analyzing glycoproteins of pancreatic cyst fluid represents a potentially valuable source for information and can benefit in differentiating mucinous from non-mucinous cysts. In glycoproteomics, specific glycoproteins and glyco-isoforms are enriched followed by matrix assisted laser desorption or liquid chromatography mass spectrometry analysis.…”
Section: Introductionmentioning
confidence: 99%
“…9-11 Investigating and analyzing glycoproteins of pancreatic cyst fluid represents a potentially valuable source for information and can benefit in differentiating mucinous from non-mucinous cysts. In glycoproteomics, specific glycoproteins and glyco-isoforms are enriched followed by matrix assisted laser desorption or liquid chromatography mass spectrometry analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of the cyst fluid proteome demonstrated that proteomic profiling of mucin in cyst fluid (obtained by EUS-FNA) was 98% accurate for pre-malignant and malignant cysts [64] . A study of select proteins in 22 cyst fluid samples identified a 3 biomarker panel of protein glycoforms that was 91% accurate for mucinous cysts [65] . Metabolomic analysis has demonstrated that metabolites, glucose and kynurenine, were lower in mucinous cysts compared to non-mucinous cysts [66] .…”
Section: Eus-fnamentioning
confidence: 99%
“…Endorepellin has been also identified in the fetal bovine rib growth plate [196], and in proteomic studies of chronic allograft nephropathy [197]. More recently, full-length endorepellin has been identified in pancreatic cysts [198]. …”
Section: Perlecan a Large Multimodular Heparan Sulfate Proteoglycanmentioning
confidence: 99%